Management of sinistra buccal abscess caused by pulp gangrene: Penatalaksanaan abses bukalis sinistra yang disebabkan oleh gangren pulpa - Asty R. Bennu; Abul Fauzi; Andi Tajrin (Makassar Dental Journal PDGI Makassar, 2024)
This case report aims to discuss the management of a buccal abscess caused by a pulp gangrene tooth in a 29-year-old woman who came with complaints of swelling accompanied by pain in the left cheek which was felt 2 days ago before entering the hospital. The management in this case was by extracting the causative tooth, namely pulp gangrene tooth 36 and intra oral incision which was carried out by installing a drain at the intraoral incision. The results of this patient's treatment showed significant improvement where the patient no longer complained of pain and the swelling had begun to decrease. It is concluded that abscess management should be done as early as possible to prevent the spread of infection.